Third Five Year Plan of Andaman and Nicobar Islands Programme for 1965-66 - Planning Commission (Planning Commission, 1965)
This publication has been brought out with a view to presenting a consolidated and detailed account of the various schemes which form part of the development programme to be undertaken in these Islands during 1965-66, which is the last year of the Third Five Year Plan. Besides, this publication also contains an account of the achievements in terms of physical and financial targets during the first four years of the Third Plan. Against the total Third Plan outlay of Rs.1021,900 lakhs(including development of Minor Ports) , the expenditure incurred during the first 4 years amounted to Rs.510,260 lakhs.
Andaman and Nicobar Administration
Andaman and Nicobar Administration